Myocardial inflammation in ischaemic and non-ischaemic heart failure relates to impaired mitochondria. (3rd October 2022) - Borger, J B; Scheiber, D; Zweck, E; Horn, P; Schultheiss, H P; Boeken, U; Akhyari, P; Lichtenberg, A; Kelm, M; Roden, M; Szendroedi, J; Westenfeld, R
Abstract: Background: Mitochondrial dysfunction is a driving factor in the development of heart failure (HF) and relates to poor cardiac function. Through elevated oxidative stress it is linked to myocardial inflammation. Both mechanisms promote the development of cardiac fibrosis, a key contributor to adverse outcomes in ischaemic and non-ischaemic HF. Differences in myocardial mitochondrial function and inflammation between patients with ischaemic and non-ischaemic HF have been indicated. While immunosuppression in non-ischaemic HF with myocardial inflammation has improved long-term results, little is known about possible benefits in ischaemic HF. Purpose: We hypothesised that: 1. Myocardial lymphocytic inflammation and fibrosis differ in patients with HF due to ischaemic cardiomyopathy (ICM) compared to patients with dilated cardiomyopathy (DCM). 2. Inflammation and fibrosis are associated with markers of mitochondrial dysfunction. Methods: Myocardial tissue specimens were obtained from the left ventricular (LV) apex of 65 patients (n[ICM] = 33, n[DCM] = 32) with HF requiring an LV assist device or heart transplantation. We assessed oxidative phosphorylation capacity (OXPHOS) via high resolution respirometry in saponine-permeabilised myocardial fibres (OROBOROS Oxygraph-2k). Reactive oxygen species (ROS) production was measured fluoroscopically via the Amplex Red method. Immunohistochemistry staining for CD3 was performed on snap-frozen tissue and digitally analysed. Azan staining was used for quantification of fibrotic area. Statistical analysis was conducted with GraphPad Prism v9.0 and IBM SPSS v27.0. Results: ICM and DCM patients did not differ significantly regarding age (60.9±5.4 vs. 55.8±12.4 years, p=0.11), sex (91% vs. 90% male, p=0.93), BMI (27.6±5.1 vs. 26.5±6.0 kg/m 2, p=0.82), or diabetic status (31% vs. 20% Type 2 Diabetes mellitus, p=0.31). Tissue specimens of ICM patients displayed about three times larger fibrotic areas compared to DCM (20.9±21.2 vs. 7.2±5.6%, p=0.001). Cellular inflammation (>14 CD3+ cells/mm 2 ) was significantly more common in ICM than DCM patients. (27 vs. 6%, p=0.024). Inflammation and fibrosis did not correlate significantly (r=0.09, p=0.46). Fibrosis was not associated with OXPHOS capacity (r=−0.129, p=0.33). In patients with inflammation, OXPHOS capacity was lower compared to patients without inflammation (92.3±40.1 vs. 131.6±55.6 pmol/(s*mg), p=0.031) and inflammation was associated with lower OXPHOS capacity (r=−0.296, p=0.019). There was a trend towards lower electron transfer capacity in patients with inflammation (98.6±43.1 vs. 129.7±48.3 pmol/(s*mg), p=0.053). ROS production was not significantly different between tissue specimens with or without inflammation (0.51±0.21 vs. 0.67±0.33 pmol/(s*ml), p=0.17). Conclusions: Myocardial cellular inflammation is prominent in ICM patients and relates to impaired mitochondria. Future studies may evaluate possible benefits from immunosuppression in ICM patients. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (DFG)